2015
DOI: 10.5539/ies.v8n6p75
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Candidate Teachers’ Beliefs Related to Knowledge, Learning and Teaching

Abstract: Candidate teachers have several beliefs related to their knowledge, learning and teaching. The purpose of this study is to analyze the beliefs of candidate teachers about knowledge, learning and teaching. Candidate teachers were assigned a scale and from the answers "belief points" were obtained based on their attitudes about these three dependent variables. It is investigated whether or not there is a significant difference in candidate teachers' belief points about knowledge, learning and teaching. In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Comparatively, those who prefer to speculate about instruction and learning in nontraditional ways are inclined to feel that knowledge is uncertain and changeable. (Bay et al, 2015). Regarding the realm of advanced beliefs concerning the certainty of knowledge, information appears to move from simplistic views of knowledge to the point of accepting that personal opinions and personal construction are important components in procuring knowledge.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Comparatively, those who prefer to speculate about instruction and learning in nontraditional ways are inclined to feel that knowledge is uncertain and changeable. (Bay et al, 2015). Regarding the realm of advanced beliefs concerning the certainty of knowledge, information appears to move from simplistic views of knowledge to the point of accepting that personal opinions and personal construction are important components in procuring knowledge.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the studies, it has been revealed that distance education is not only a technical situation but also involves different pedagogical challenges (Ali, 2020) and that distance education applied in the epidemic should be supported not only by technological infrastructure but also by mental transformation (Bozkurt, 2020). However, it has emerged that the knowledge and skills that teachers should have in distance education are not sufficient alone and teachers' interest in the program affects the implementation processes of their feelings and thoughts about the program (Deniz, 2021;Yavuz & Toprakçı, 2021) Considering that the beliefs of individuals on subjects such as knowledge, learning, and teaching are related to each other (Bay et al, 2015) and that the attitude of the person towards the work they do affects their work performance (Kahramanoğlu et al, 2018), it has become a necessity to determine and evaluate the attitude levels of teachers working in the primary and secondary education levels who have an important role in distance education. Fırat, Kılınç, and Yüzer (2018) stated in their study that internal motivation has a decisive importance in online training and teachers have negative perceptions about distance education.…”
Section: Introductionmentioning
confidence: 99%
“…Teachers' interest in distance education, their thoughts and feelings about the program, and how they evaluate distance education greatly affect the implementation process of the program. It is known that successful distance education can only be achieved with teachers who can provide quality education (Tabata & Johnsrud, 2008) and individual beliefs about knowledge, learning and teaching are interconnected (Bay et al, 2015). For all these reasons, it has become a need to determine teachers' attitudes towards distance education, who have an important role as the practitioner of the program.…”
mentioning
confidence: 99%